Separator substrate for electrochemical device and separator including same

The use of a crosslinked polyolefin resin with chromium and a heat-starting agent in the separator substrate addresses thermal instability and short circuit risks in lithium-ion batteries, improving safety and performance.

JP2025502790AActive Publication Date: 2025-01-28LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024539360
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-07-12
Publication Date
2025-01-28
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

Lithium-ion batteries face issues with fire and explosion risks due to organic electrolytes, complex manufacturing processes, and insufficient discharge capacity at low temperatures, particularly in secondary batteries, which also suffer from thermal instability and potential short circuits due to polyolefin separator materials.

Method used

A separator substrate composed of bridged polyolefin resin with chromium (Cr) and a crosslinking structure formed by radical polymerization using a heat-starting agent, enhancing thickness and heat resistance, and incorporating inorganic particles and a binder to improve stability.

Benefits of technology

The proposed separator substrate improves uniformity and heat resistance, reducing the risk of thermal runaway and short circuits, thereby enhancing the safety and performance of electrochemical elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502790000001
    Figure 2025502790000001
  • Figure 2025502790000002
    Figure 2025502790000002
  • Figure 2025502790000003
    Figure 2025502790000003
Patent Text Reader

Abstract

The present invention relates to a separator substrate, a separator, and an electrochemical element including the same. The separator substrate of the present invention is a separator substrate for an electrochemical element including a crosslinked polyolefin resin and chromium (Cr), the separator substrate having a gel fraction of 3% to 80%, a standard deviation (Δd) of thickness measured at any one of at least 100 points being 0.5 μm or less, and a thickness of 1 m 2 The number of spots with a long side length of 50 μm or more per unit area shall be 10 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator substrate for an electrochemical device, a separator including the same, and an electrochemical device including the same.

[0002] This application claims priority to Korean Patent Application No. 2022-0085967 filed on July 12, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings of that application. [Background technology]

[0003] Secondary batteries, such as lithium-ion secondary batteries, are widely used as power sources for portable electronic devices such as notebook computers, mobile phones, digital cameras, video cameras, etc. Recently, these batteries have been applied to a wide range of fields, such as automobiles, because of their characteristic of having high energy density.

[0004] Lithium secondary batteries have been in the limelight due to their advantages of higher operating voltage and much higher energy density compared to conventional batteries using aqueous electrolytes such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries. However, lithium ion batteries have safety issues such as fire and explosion due to the use of organic electrolytes, and are complicated to manufacture. Although recent lithium ion polymer batteries have improved the weaknesses of lithium ion batteries and are counted as one of the next-generation batteries, their battery capacity is still relatively low compared to lithium ion batteries, and in particular, their discharge capacity at low temperatures is insufficient, and there is an urgent need to improve this.

[0005] It is very important to evaluate the stability and ensure the safety of such electrochemical elements. In terms of the safety characteristics of electrochemical elements, there is a high concern that an explosion may occur if the electrochemical element overheats, causing thermal runaway, or if the separator is penetrated. In particular, polyolefin separator substrates that are commonly used as separators for electrochemical elements have a problem in that they exhibit extremely severe thermal shrinkage behavior at temperatures above 100°C due to the characteristics of the material and the characteristics of the manufacturing process, including stretching, which causes a short circuit between the positive and negative electrodes.

[0006] In order to solve such safety problems of electrochemical devices, a separator has been proposed in which a porous inorganic coating layer is formed by coating at least one side of a separator substrate having a large number of pores with a mixture of an excess amount of inorganic particles and a binder polymer, but there is currently a constantly increasing need for further improvement in stability. Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, the technical problem to be solved by the present invention is to provide a separator substrate having improved thickness uniformity and heat resistance, and a separator using the same having improved thickness uniformity and heat resistance, thereby providing an electrochemical device having improved stability and excellent resistance characteristics. [Means for solving the problem]

[0008] In order to solve the above problems, according to one aspect of the present invention, there is provided a separator substrate having the following features.

[0009] The separator substrate according to the first aspect is a separator substrate for an electrochemical element, which contains a crosslinked polyolefin resin and chromium (Cr), and the separator substrate has a gel fraction of 3% to 80%, a standard deviation (Δd) of thickness measured at any one of at least 100 points is 0.5 μm or less, and a thickness of 1 m is 0.5 μm or less.2 The number of spots with a long side length of 50 μm or more per unit area shall be 10 or less.

[0010] According to the second aspect, in the first aspect, the separator substrate may have a gel fraction of 3% to 50%.

[0011] According to a third aspect, in the first or second aspect, the chromium content may be 0.1 to 20 ppm.

[0012] According to the fourth aspect, in any one of the first to third aspects, the crosslinked structure in the crosslinked polyolefin resin may include a structure resulting from a radical polymerization reaction between vinyl groups mediated by a thermal initiator.

[0013] According to a fifth aspect, in any one of the first to fourth aspects, the thermal initiator may include a peroxide-based compound, a persulfate-based compound, an azo-based compound, or a mixture thereof.

[0014] According to a sixth aspect, in any one of the first to fifth aspects, the separator substrate for an electrochemical element may further contain at least one of titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), and vanadium (V).

[0015] According to the seventh aspect, in any one of the first to sixth aspects, the standard deviation (Δd) of thickness measured at any one of at least 100 points on the separator substrate may be 0.3 μm or less.

[0016] According to another aspect of the present invention, there is provided a method for producing a separator substrate having the following features.

[0017] A method for producing a separator substrate according to an eighth aspect includes the steps of melt-extruding a raw material containing a polyolefin resin to obtain a polymer melt extrudate, molding and stretching the obtained polymer melt extrudate to obtain a polymer sheet, applying a coating liquid containing a thermal initiator to the polymer sheet, and drying and heat-setting the polymer sheet coated with the coating liquid, wherein the polyolefin resin includes a polyolefin resin produced using an olefin polymerization catalyst containing chromium, and the gel fraction of the separator substrate is 3% to 80%.

[0018] According to a ninth aspect, in the eighth aspect, the polyolefin resin in the raw material may include a polyolefin resin having 100 or more terminal vinyl groups per 1 million carbon atoms.

[0019] According to a tenth aspect, in the eighth or ninth aspect, the raw material may further include a polyolefin resin produced using an olefin polymerization catalyst that does not contain chromium and contains titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), vanadium (V), or two or more of these.

[0020] According to an eleventh aspect, in any one of the eighth to tenth aspects, the content of the polyolefin resin produced using an olefin polymerization catalyst containing chromium may be 10% by weight or more based on the total weight of the polyolefin resin in the raw material.

[0021] According to still another aspect of the present invention, there is provided a separator having the following embodiment.

[0022] A separator according to a twelfth aspect includes the separator substrate according to any one of the first to seventh aspects and an inorganic coating layer formed on at least one surface of the separator substrate, the inorganic coating layer including inorganic particles and a binder material.

[0023] According to yet another aspect of the present invention, there is provided an electrode assembly having the following configuration.

[0024] The electrode assembly according to the thirteenth aspect includes a positive electrode, a negative electrode, and a separator sandwiched between the positive electrode and the negative electrode, the separator being as described in the twelfth aspect. Effect of the Invention

[0025] The separator substrate according to one embodiment of the present invention has a large amount of crosslinked structures in the polyolefin chain, which improves the thickness uniformity and heat resistance, thereby significantly improving the operational stability, such as the heat resistance, of an electrochemical device including a separator using such a separator substrate.

[0026] In particular, the separator substrate according to one embodiment of the present invention is prepared by using a polyolefin resin containing a large amount of vinyl groups at its terminals, which is prepared by using an olefin polymerization catalyst containing chromium, and a thermal initiator for crosslinking between the vinyl groups at its terminals. The separator substrate has a large amount of crosslinked structures between polyolefin chains, which can improve the thickness uniformity and heat resistance, but the mechanism of the present invention is not limited thereto. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The present invention will be described in detail below.

[0028] The present invention relates to a separator substrate for an electrochemical device, a separator including the separator, and an electrochemical device including the separator. In the present invention, the electrochemical device is a device that converts chemical energy into electrical energy by an electrochemical reaction, and is a concept that encompasses primary batteries and secondary batteries. The secondary battery is capable of charging and discharging, and is a concept that encompasses lithium ion batteries, nickel-cadmium batteries, nickel-hydrogen batteries, etc.

[0029] First, a separator substrate for an electrochemical device according to one embodiment of the present invention will be described in detail.

[0030] A separator substrate for an electrochemical element according to one aspect of the present invention is a separator substrate for an electrochemical element comprising a crosslinked polyolefin resin and chromium (Cr), the separator substrate having a gel fraction of 3% to 80%, a standard deviation (Δd) of thickness measured at any one of at least 100 points being 0.5 μm or less, and a thickness of 1 m 2 There are 10 or fewer spots with a long side length of 50 μm or more per unit area.

[0031] According to one embodiment of the present invention, the polyolefin resin is not particularly limited in terms of its monomer as long as it is used as a porous separator substrate. For example, the polyolefin resin may be a homopolymer of a monomer selected from polyethylene, polypropylene, polybutylene, polypentene, polyhexene, polyoctene, ethylene, propylene, butene, pentene, 4-methylpentene, hexene, and octene; a copolymer of two or more of these; or a mixture thereof, but is not limited thereto.

[0032] As described later in the section on the manufacturing method of the separator substrate in this specification, the polyolefin resin contains a polyolefin resin manufactured using an olefin polymerization catalyst containing chromium (Cr), and thus the separator substrate according to one embodiment of the present invention contains chromium (Cr). Specifically, the separator substrate contains chromium as a residue of the chromium catalyst used in the polymerization of the polyolefin resin.

[0033] In one embodiment of the present invention, the chromium-containing olefin polymerization catalyst may contain, for example, chromium oxide; and a support supporting the chromium oxide. The support may contain, for example, at least one component selected from the group consisting of silica, titania, alumina, zirconia, and aluminum phosphate; however, the present invention is not limited thereto.

[0034] In one embodiment of the present invention, the content of chromium contained in the separator substrate may be, for example, 0.1 ppm to 20 ppm, 1 ppm to 10 ppm, or 5 ppm to 10 ppm, but is not limited thereto. The content of chromium in the separator substrate may be, for example, a value measured using an inductively coupled plasma mass spectrometer (ICP-MS). When the content of chromium contained in the separator substrate is within the above-mentioned range, there may be advantageous effects in terms of the number of vinyl groups in the polyolefin resin before crosslinking and the crosslinking degree of the crosslinked polyolefin resin produced using the same, but the present invention is not limited thereto.

[0035] According to one embodiment of the present invention, the polyolefin resin produced using the chromium-containing olefin polymerization catalyst is characterized by containing a large amount of terminal vinyl groups in an active state that can be crosslinked by a thermal initiator in a subsequent process, and thus the separator substrate can include a polyolefin resin in which multiple crosslinked structures are formed between polyolefin chains through a crosslinking reaction by a thermal initiator.

[0036] In this specification, the "crosslinked polyolefin resin" refers to a polyolefin resin in which vinyl groups present in the chains of the polyolefin resin used as a raw material for the separator substrate are activated by an initiation reaction, thereby forming a crosslinked structure within and / or between the chains of the polyolefin resin.

[0037] Specifically, the crosslinked polyolefin resin is produced by activating a vinyl group present at one end of a polyolefin chain with a thermal initiator to form a radical, and the formed radical reacts with a radical formed in a polyolefin chain of another molecule and / or a radical formed at the other end of the polyolefin chain of the same molecule to form C(Sp 2 )-C(Sp 2 ) linked cross-linked structures.

[0038] As a result, the crosslinked polyolefin resin can contain no terminal vinyl groups at all, or can contain a number of terminal vinyl groups that is reduced compared to the number of terminal vinyl groups present in the polyolefin resin before crosslinking.

[0039] From the substantially same viewpoint, the crosslinked polyolefin resin has a C(Sp 2 )-C(Sp 2 ) bonds, the number of C(Sp 2 )-C(Sp 2 ) bonds.

[0040] In one embodiment of the present invention, the polyolefin resin produced using the chromium-containing olefin polymerization catalyst is analyzed by a nuclear magnetic resonance spectrometer (Bruker 500 NMR, 14.1 tesla). 1 When the number of functional groups is confirmed from the H-NMR spectrum, the polymer may contain 100 or more, 200 or more, 300 or more, 400 or more, 500 or more, 600 or more, 700 or more, 800 or more, 900 or more, or 950 or more terminal vinyl groups per 1 million carbons. The upper limit of the terminal vinyl groups may be 1,500 or less, or 1,000 or less within the above-mentioned range, but is not limited thereto.

[0041] Thus, in one embodiment of the present invention, the number of terminal vinyl groups of the polyolefin resin before crosslinking may be, for example, 100 or more, 200 or more, 300 or more, 400 or more, 500 or more, 600 or more, 700 or more, 800 or more, 900 or more, or 950 or more per million carbons.

[0042] In yet another embodiment of the present invention, when the separator substrate contains a polyolefin resin produced using another catalyst in addition to the chromium-containing olefin polymerization catalyst, the number of terminal vinyl groups of the polyolefin resin before crosslinking and the content of terminal vinyl groups of the polyolefin resin before crosslinking are preferably measured based on the number of terminal vinyl groups and the content of terminal vinyl groups of the entire polyolefin resin.

[0043] As described above, the crosslinked structures in the crosslinked polyolefin resin include structures resulting from radical polymerization reactions between vinyl groups mediated by a thermal initiator.

[0044] In one embodiment of the present invention, the thermal initiator can be used without limitation as long as it is an initiator capable of forming radicals by activating a vinyl group present in the polyolefin chain. Specifically, it can be used without limitation as long as it is an initiator capable of forming radicals by activating a terminal vinyl group present in the polyolefin chain. The thermal initiator can include, for example, a peroxide-based compound, a persulfate-based compound, an azo-based compound, or a mixture thereof.

[0045] Examples of the peroxide compound include, but are not limited to, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (DHBP), benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, dicumyl peroxide, cumyl peroxide, hydrogen peroxide (hydrogen peroxide), and mixtures of two or more of these.

[0046] The persulfate compound contains peroxymonosulfate ion (SO5 2- ) and peroxydisulfate (S2O8 2- The persulfate compound is not particularly limited as long as it contains at least one of the following: sodium peroxymonosulfate (Na2SO5), potassium peroxymonosulfate (KHSO5), sodium peroxydisulfate (Na2S2O8), ammonium peroxydisulfate ((NH4)2S2O8), potassium peroxydisulfate (K2S2O8), or a mixture of two or more of these, but is not limited thereto.

[0047] The azo compound may include, for example, 2,2'-azobis(2-methylpropionitrile, AIBN), but is not limited thereto.

[0048] In one embodiment of the present invention, the separator substrate may further contain a polyolefin resin produced from another type of olefin polymerization catalyst in addition to the polyolefin resin produced from the chromium-containing olefin polymerization catalyst as described above.

[0049] The other type of olefin polymerization catalyst may be, for example, an olefin polymerization catalyst containing at least one of titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), and vanadium (V).Therefore, the separator substrate may further contain, for example, at least one of titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), and vanadium (V).

[0050] In one embodiment of the present invention, the other type of olefin polymerization catalyst can be, for example, a metallocene catalyst, a Ziegler-Natta catalyst, or a mixture thereof, but the present invention is not limited thereto.

[0051] In this specification, the polyolefin resin produced using the chromium-containing olefin polymerization catalyst may be named "Cr-type polyolefin", and the polyolefin resin produced using the other types of olefin polymerization catalyst may be named "ZT-type polyolefin".

[0052] In one embodiment of the present invention, when the separator substrate contains a polyolefin resin produced using an olefin polymerization catalyst containing chromium as well as a polyolefin resin produced using another type of olefin polymerization catalyst, the weight ratio of the Cr-type polyolefin and the ZT-type polyolefin may be, for example, 1:9 to 9:1, specifically, 2:8 to 8:2, 3:7 to 7:3, or 3:7 to 5:5, but is not limited thereto. When the separator substrate contains both the Cr-type polyolefin and the ZT-type polyolefin, it may be advantageous in that the molecular weight of the separator substrate can be improved by the ZT-type polyolefin having a high molecular weight, but the present invention is not limited thereto.

[0053] In one embodiment of the present invention, the weight ratio of Cr-type polyolefin and ZT-type polyolefin in the separator substrate, expressed as the value of Cr-type polyolefin:ZT-type polyolefin, may be, for example, 10:0 (i.e., ZT-type polyolefin is not included) to 1:9, and more specifically, may be 10:0 to 5:5, 1:9 to 5:5, 10:0 to 3:7, 1:9 to 3:7, or 3:7 to 5:5, but the present invention is not limited thereto.

[0054] In one embodiment of the present invention, the separator substrate may further contain, in addition to polyolefin, at least one polymer resin such as polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalene, etc. Examples of the separator substrate include, but are not limited to, nonwoven fabric, porous polymer film, or a laminate of two or more of these.

[0055] In one embodiment of the present invention, as described below, the separator substrate comprises a polyolefin resin produced using an olefin polymerization catalyst containing chromium, and when a polyolefin sheet derived from the polyolefin resin is heat-set during the manufacturing process of the separator substrate, a crosslinked structure is formed within and / or between chains in the polyolefin resin by a radical polymerization reaction mediated by the thermal initiator, thereby improving not only the thickness uniformity and heat resistance of the separator substrate but also the appearance characteristics of the separator substrate, but the mechanism of the present invention is in no way limited thereto.

[0056] The separator substrate according to one embodiment of the present invention exhibits a gel fraction of 3% to 80%. This may be a characteristic that appears when the separator substrate contains a polyolefin resin having a very high degree of crosslinking, but the characteristics of the present invention are not limited thereto. The gel fraction of the separator substrate may be, for example, 3% to 70%, 3% to 60%, 3% to 50%, 3% to 45%, 3% to 40%, 3% to 30%, 3% to 20%, or 3% to 10%.

[0057] As described above, one of the features of the polyolefin resin is that it exhibits a high degree of crosslinking due to the crosslinked structure formed within and / or between polyolefin chains, and thus, while the polyolefin resin before crosslinking is dissolved in a benzene-based solvent, the crosslinked polyolefin resin exhibits a characteristic that allows the gel fraction to be measured without being dissolved in a benzene-based solvent.

[0058] In the present specification, the gel fraction may be measured according to the following method. First, 0.2 g of a separator substrate specimen to be measured is placed in a 120 mesh stainless steel net, extracted in trichlorobenzene at 100° C. for 12 hours, and then dried in a vacuum oven at 100° C. for 12 hours. Then, the weight of the specimen remaining on the stainless steel net is measured, and the gel fraction is measured according to the following formula. The gel fraction may be expressed as an average value of the measured values ​​for three specimens to improve the accuracy of the measurement. Gel fraction (%) = {(remaining specimen weight (g)) / 0.2 g} x 100

[0059] In one embodiment of the present invention, the separator substrate has a standard deviation (Δd) of thickness measured at any one of at least 100 points of 0.5 μm or less, thereby achieving an outstanding improvement in thickness uniformity.

[0060] In one embodiment of the present invention, the standard deviation (Δd) of the thickness measured at any one of at least 100 points on the separator substrate may be, for example, 0.45 μm or less, 0.40 μm or less, 0.35 μm or less, 0.3 μm or less, or 0.25 μm or less. The closer the standard deviation is to 0, the greater the uniformity of the thickness, so the lower limit of the standard deviation of the thickness may be 0.

[0061] The thickness of the separator substrate may be measured according to a method for measuring the thickness of the separator substrate, and may be, for example, a value measured by analyzing a scanning electron microscope (SEM) image of the produced separator substrate, or by using a known thickness measuring device. As the thickness measuring device, for example, VL-50S-B (manufactured by Mitutoyo Corporation) can be used, but is not limited thereto.

[0062] In general, when preparing a separator substrate, if raw materials such as polymer resins, diluents, crosslinking agents, and other additives are all charged into an extruder and reacted together, problems have been observed in that side reactions occur in the extruder, or raw materials that are not melted due to insufficient kneading between the raw materials cause spots on the surface of the separator substrate that have a difference in brightness compared to the surrounding area.

[0063] In this specification, the "spots" refer to areas on the surface of the separator substrate that have a white spot shape due to a higher brightness and lower transparency compared to the surrounding area.

[0064] In one embodiment of the present invention, the number of spots may be assessed by visual observation or by observation under a microscope such as a scanning electron microscope (SEM).

[0065] According to one embodiment of the present invention, the separator substrate is prepared by adding a polyolefin resin as a raw material, forming the polyolefin sheet, and then adding a thermal initiator, thereby suppressing the occurrence of the above-mentioned spots to a minimum and improving the defect resistance of the appearance. For example, the separator substrate can be prepared by forming a polyolefin sheet from a polyolefin resin as a raw material, and then adding a thermal initiator. 2 The number of spots having a long side length of 50 μm or more per unit area may be 10 or less. Specifically, the number of spots under the above conditions may be 0 to 7, 0 to 5, or 0 to 3. By forming the number of spots within the above range, it is possible to achieve an advantageous effect in terms of preventing the occurrence of uncoated areas and shorts in batteries due to appearance defects in future ceramic coating.

[0066] In another embodiment of the present invention, the thickness of the separator substrate may be, for example, 4 μm to 20 μm. When the thickness of the separator substrate is in the above-mentioned range, advantageous effects can be exhibited in terms of the conductive barrier function and the resistance of the separator, but the present invention is not limited thereto.

[0067] In one embodiment of the present invention, the weight average molecular weight (Mw) of the polyolefin resin contained in the separator substrate may be, for example, in the range of 100,000 g / mol to 5,000,000 g / mol. When the weight average molecular weight of the polyolefin resin is in the above-mentioned range, advantageous effects can be exhibited in terms of ensuring mechanical properties and shutdown characteristics of the separator substrate, but the present invention is not limited thereto.

[0068] In one embodiment of the present invention, the weight average molecular weight of the Cr-type polyolefin may be, for example, in the range of 100,000 g / mol to 600,000 g / mol, 100,000 g / mol to 400,000 g / mol, or 150,000 g / mol to 350,000 g / mol. The weight average molecular weight of the ZT-type polyolefin may be, for example, in the range of 400,000 g / mol to 2,000,000 g / mol, 400,000 g / mol to 1,500,000 g / mol, 500,000 g / mol to 1,500,000 g / mol, or 600,000 g / mol to 1,200,000 g / mol. As described above, polyolefins produced using different catalysts can be characterized by having completely different molecular weight ranges, and the present invention can exhibit the effect of further improving the physical properties of the separator substrate by using two polyolefins having different molecular weight scales as described above, but the present invention is not limited thereto.

[0069] In this specification, the weight average molecular weight (Mw) of the polyolefin resin can be measured using gel permeation chromatography (GPC, PL-GPC 220, manufactured by Agilent Technologies, Inc.) under the following conditions. -Column: PL Olexis (Polymer Laboratory) -Solvent: Trichlorobenzene (TCB) -Flow rate: 1.0ml / min -Sample concentration: 1.0mg / ml -Injection volume: 200μl -Column temperature: 160°C -Detector: Agilent High Temperature RI detector -Standard: Polystyrene (corrected to a cubic function)

[0070] In one embodiment of the present invention, the separator substrate may have a porous structure, for example, a pore diameter of 0.01 μm to 0.10 μm and a porosity of 30 vol% to 70 vol%. When the pore diameter and porosity in the separator substrate are within the above-mentioned ranges, advantageous effects can be exhibited in terms of the ion permeability and mechanical strength of the separator, but the present invention is not limited thereto. The pore diameter and porosity of the separator substrate can be measured according to a known method, for example, using a BELSORP series instrument (e.g., BELSORP mini II) manufactured by BEL Japan.

[0071] In one embodiment of the present invention, the separator substrate may exhibit excellent heat resistance. For example, the separator substrate may exhibit a breaking temperature of 155°C or more. For example, the breaking temperature of the separator substrate may be 160°C or more, 170°C or more, 180°C or more, 190°C or more, 195°C or more, or even 200°C or more. The higher the breaking temperature of the separator substrate, the more heat resistant it is, so the upper limit of the breaking temperature of the separator substrate is not particularly limited, and may be, for example, 500°C or less, 450°C or less, 350°C or less, or 300°C or less.

[0072] In the present specification, the breaking temperature of the separator substrate is measured by applying a load of 0.01 N to a separator substrate specimen to be measured using a thermal mechanical analyzer (TMA) and observing the degree of deformation while raising the temperature at a rate of 5° C. / min. The breaking temperature of the separator substrate may be measured as the temperature at which the separator substrate shrinks as the temperature rises and then breaks as it expands again.

[0073] The separator substrate for an electrochemical element according to one embodiment of the present invention as described above has an effect of improving appearance characteristics, thickness uniformity, and heat resistance by forming a crosslinked structure between polyolefin chains by using a thermal initiator during heat fixing of a polyolefin resin produced using an olefin polymerization catalyst containing chromium and a polyolefin sheet stretched from the polyolefin resin, but the present invention is not limited thereto.

[0074] Next, a method for producing a separator substrate for an electrochemical device according to another embodiment of the present invention will be described in detail.

[0075] According to another aspect of the present invention, a separator substrate for an electrochemical device includes the steps of melt-extruding a raw material including a polyolefin resin to obtain a polymer melt extrudate, forming and stretching the obtained polymer melt extrudate to obtain a polymer sheet, applying a coating liquid including a thermal initiator to the polymer sheet, and drying and heat-setting the polymer sheet to which the coating liquid is applied, wherein the polyolefin resin includes a polyolefin resin produced using an olefin polymerization catalyst containing chromium.

[0076] First, a raw material containing a polyolefin resin produced using the chromium-containing olefin polymerization catalyst is melt-extruded to obtain a polymer melt extrudate.

[0077] In one embodiment of the present invention, for the melt extrusion, the raw materials preferably include a diluent as well as the polyolefin resin produced using the chromium-containing olefin polymerization catalyst.

[0078] The diluent may be, for example, liquid or solid paraffin oil, mineral oil, wax, soybean oil, or the like that is commonly used in the manufacture of wet separators.

[0079] In one embodiment of the present invention, the diluent may be a diluent capable of liquid-liquid phase separation from the polyolefin resin. For example, phthalic acid esters such as dibutyl phthalate, dihexyl phthalate, and dioctyl phthalate; diphenyl ether, benzyl ether, and the like may be used. fatty acids having 10 to 20 carbon atoms, such as palmitic acid, stearic acid, oleic acid, linoleic acid, and linolenic acid; fatty acid alcohols having 10 to 20 carbon atoms, such as palmitic alcohol, stearic alcohol, and oleic alcohol; saturated and unsaturated fatty acids having a fatty acid group with 4 to 26 carbon atoms, such as palmitic acid mono-, di-, or triester, stearic acid mono-, di-, or triester, oleic acid mono-, di-, or triester, and linoleic acid mono-, di-, or triester, or fatty acid esters in which one or more fatty acids in which the double bond of an unsaturated fatty acid is substituted with epoxy, have 1 to 8 hydroxy groups and are ester-bonded with an alcohol having 1 to 10 carbon atoms; or a mixture of two or more of these may be used, but the present invention is not limited to these.

[0080] In one embodiment of the present invention, the content of the diluent may be, for example, 100 parts by weight to 350 parts by weight, or 125 parts by weight to 300 parts by weight, or 150 parts by weight to 250 parts by weight, based on 100 parts by weight of the polyolefin. When the total content of the diluent satisfies the above numerical range, problems such as reduced porosity, small pore size, and less interconnection between pores, which significantly reduces permeability, and increased extrusion load due to increased viscosity of the polyolefin composition, which makes it difficult to process, can be prevented, and problems such as breakage and thickness variation during stretching caused by reduced kneading between polyolefin and diluent due to low polyolefin content, which is extruded in a gel state without being thermodynamically kneaded with the diluent, can be prevented, but the present invention is not limited thereto.

[0081] In one embodiment of the present invention, the raw materials may further include, in addition to the polyolefin resin produced using the chromium-containing olefin polymerization catalyst and the diluent, polyolefin resins produced using other types of olefin polymerization catalysts, for example, Ziegler-Natta catalysts; or olefin polymerization catalysts containing titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), vanadium (V), or two or more thereof; and other polymer resins, and the above description is incorporated herein by reference with respect to these polyolefin resins and other polymer resins.

[0082] For example, in one embodiment of the present invention, the raw material may further include a polyolefin resin produced by an olefin polymerization reaction using a Ziegler-Natta catalyst.

[0083] According to one embodiment of the present invention, the weight ratio of the polyolefin resin (Cr-type polyolefin) produced using an olefin polymerization catalyst containing chromium and the polyolefin resin (ZT-type polyolefin) produced using another type of olefin polymerization catalyst in the raw materials may be 1:9 to 9:1, specifically, 2:8 to 8:2, 3:7 to 7:3, or 5:5, but the present invention is not limited thereto.

[0084] According to another embodiment of the present invention, when ZT type polyolefin is further included in addition to the Cr type polyolefin, the content of the polyolefin resin produced using the chromium-containing olefin polymerization catalyst based on the total 100% by weight of the raw materials may be, for example, 10% by weight or more. Specifically, the content of the polyolefin resin produced using the chromium-containing olefin polymerization catalyst based on the total 100% by weight of the raw materials may be 15% by weight or more, 20% by weight or more, 25% by weight or less, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, 50% by weight or more, and / or 99.9% by weight or less, 99% by weight or less, 95% by weight or less, or 90% by weight or less, but the present invention is not limited thereto.

[0085] In one embodiment of the present invention, in the step of obtaining the polymer melt extrudate, a general single screw extruder or twin screw extruder can be used, but is not limited thereto.

[0086] The resulting polymeric melt extrudate is then shaped and stretched to obtain a polymeric sheet.

[0087] In one embodiment of the present invention, after extrusion of the polymer melt extrudate, a cooled extrudate may be formed using a conventional casting or calendaring method using a method such as water cooling or air cooling.

[0088] In one embodiment of the present invention, the molding and stretching steps provide a separator substrate having improved mechanical strength and puncture strength.

[0089] In one embodiment of the present invention, the stretching may be performed by sequential or simultaneous stretching using a roll or a tenter. The stretching ratio may be, for example, 3 times or more, or 5 to 12 times in each of the longitudinal and transverse directions, and the total stretching ratio may be 20 to 120 times. When the stretching ratio satisfies the above numerical range, advantageous effects can be exhibited in terms of the uniformity of the thickness of the separator substrate to be manufactured and the balance of physical properties between the longitudinal and transverse directions, but the present invention is not limited thereto.

[0090] In one embodiment of the present invention, the stretching temperature may vary depending on the melting point of the polyolefin resin used, and the concentration and type of the diluent, but the present invention is not limited thereto.

[0091] The diluent is then extracted from the stretched polymer sheet to obtain a porous polymer sheet.

[0092] In one embodiment of the present invention, the diluent may be extracted from the stretched sheet using an organic solvent that is highly soluble in the diluent, and the resulting sheet may be dried to form a porous sheet.

[0093] The organic solvent is not particularly limited as long as it can extract the diluent used. From the viewpoints of extraction efficiency and drying speed, methyl ethyl ketone, methylene chloride, hexane, etc. can be used.

[0094] In one embodiment of the present invention, the extraction method may be any of the conventional solvent extraction methods, such as an immersion method, a solvent spray method, an ultrasonic method, etc., which may be used separately or in combination. In one embodiment of the present invention, the content of the residual diluent after the extraction treatment may be preferably 1 wt% or less. When the content of the residual diluent is within the above-mentioned range, advantageous effects can be exhibited in terms of the permeability and mechanical properties of the separator substrate to be manufactured, and the efficiency of the manufacturing process, but the present invention is not limited thereto.

[0095] The extraction time and extraction temperature may vary depending on the thickness of the polymer sheet and the type of polymer, and the present invention is not limited thereto.

[0096] A coating solution containing a thermal initiator is then applied to the polymer sheet.

[0097] In the present invention, a coating liquid containing a thermal initiator is applied to a polymeric porous sheet with exposed pores. As described above, the thermal initiator is capable of activating the vinyl groups at the ends of the polyolefin resin chains to form radicals. This not only allows the thermal initiator to form a large amount of crosslinked structures in the polyolefin chains, but also allows the coating liquid to penetrate into the fibrils present on the surfaces of the already formed pores, thereby providing an outstanding effect in terms of improving the heat resistance of the separator substrate, but the present invention is not limited thereto.

[0098] In one embodiment of the present invention, the coating liquid may further contain conventional additives for improving specific functions, such as a surfactant, an oxidation stabilizer, a UV stabilizer, an antistatic agent, a nucleating agent, etc., if necessary, but the present invention is not limited thereto.

[0099] Then, the polymer sheet coated with the coating liquid is dried and heat-set to obtain a separator substrate.

[0100] The heat fixing is performed to fix the porous membrane and apply heat to forcibly hold the porous membrane that tends to shrink, thereby removing residual stress.

[0101] According to the method for producing a separator substrate of the present invention, a coating liquid containing the thermal initiator is applied before heat setting, thereby obtaining a polyolefin resin-based separator substrate in which a large amount of crosslinked structures are formed by crosslinking reactions within and / or between polyolefin chains due to radical polymerization reactions mediated by the thermal initiator during the heat setting.

[0102] In one embodiment of the present invention, the temperature and time of the heat setting may vary depending on the content of vinyl groups in the polyolefin chain and the composition of the coating liquid, but the present invention is not limited thereto.

[0103] The separator substrate produced according to the above method can have the separator substrate properties described above.

[0104] In one embodiment of the present invention, the separator substrate produced according to the above method may have a gel fraction of 3% to 80%.

[0105] In one embodiment of the present invention, the separator substrate produced according to the above method may have a standard deviation (Δd) of thickness measured at any of at least 100 locations of 0.5 μm or less.

[0106] In one embodiment of the present invention, the separator substrate produced according to the above method is 1 m 2 There may be no more than 10 spots per pixel having a long side length of 50 μm or more.

[0107] In one embodiment of the present invention, the separator substrate produced according to the above method has a gel fraction of 3% to 80%, a standard deviation (Δd) of thickness measured at any one of at least 100 points is 0.5 μm or less, and a thickness of 1 m is 0.5 μm or less.2 There may be no more than 10 spots per pixel having a long side length of 50 μm or more.

[0108] According to yet another aspect of the present invention, there is provided a separator for an electrochemical device, comprising: the separator substrate described above; and an inorganic coating layer formed on at least one surface of the separator substrate, the inorganic coating layer comprising inorganic particles and a binder material.

[0109] The inorganic coating layer may have a porous structure due to pores caused by interstitial volume between inorganic particles. The pores can have a pore size and porosity (pore volume ratio) that can be adjusted according to the particle size and particle size distribution of the particles. This structure enhances resistance to metallic foreign matter present in the electrode and suppresses shrinkage of the polyolefin separator, which is the base material, thereby enhancing the safety of the electrochemical device. In view of this, the inorganic coating layer may contain inorganic particles in a ratio of 70 wt% to 99.5 wt%, preferably 80 wt% to 99 wt%, based on 100 wt% of the inorganic coating layer.

[0110] In one embodiment of the present invention, the inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles usable in the present invention are not particularly limited as long as they do not cause oxidation and / or reduction reactions in the operating voltage range of the applied electrochemical device (e.g., 0 to 5 V based on Li / Li+). In particular, when inorganic particles with a high dielectric constant are used as the inorganic particles, they can contribute to increasing the dissociation degree of the electrolyte salt, for example, the lithium salt, in the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte solution.

[0111] For the reasons described above, it is preferable that the inorganic particles include inorganic particles having a high dielectric constant, the dielectric constant of which is 5 or more, preferably 10 or more. Non-limiting examples of inorganic particles having a dielectric constant of 5 or more include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x Lax Zr 1-y Ti y O3(PLZT, 0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, AlOOH, Al(OH)3, SiC and TiO2, and any one or more of these may be included.

[0112] In one embodiment of the present invention, the average particle size (D 50 Although there is no particular limitation for the thickness of the inorganic coating layer, it is preferably in the range of 0.1 μm to 2.5 μm in order to form an inorganic coating layer with a uniform thickness and to have a suitable porosity.

[0113] In one embodiment of the present invention, the binder material may include an acrylic polymer and / or a PVDF polymer. The acrylic polymer may include, for example, a (meth)acrylic polymer. The (meth)acrylic polymer is a monomer containing a (meth)acrylic acid ester, and examples of such monomers include monomers such as butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-oxyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate, and one or more of these may be included. The PVdF-based polymer may include at least one of a homopolymer of vinylidene fluoride (i.e., polyvinylidene fluoride), a copolymer of vinylidene fluoride and a copolymerizable monomer, and a mixture thereof. In one embodiment of the present invention, the monomer may be, for example, a fluorinated monomer and / or a chlorine-based monomer. Non-limiting examples of the fluorinated monomer include vinyl fluoride; trifluoroethylene (TrFE); chlorofluoroethylene (CTFE); 1,2-difluoroethylene; tetrafluoroethylene (TFE); hexafluoropropylene (HFP); perfluoro(alkyl vinyl) ethers such as perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE), and perfluoro(propyl vinyl) ether (PPVE); perfluoro(1,3-dioxole), and perfluoro(2,2-dimethyl-1,3-dioxole) (PDD), and any one or more of these may be included.In one embodiment of the present invention, the PVDF-based polymer may include at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-chlorofluoroethylene (PVDF-CTFE), polyvinylidene fluoride-tetrafluoroethylene (PVdF-TFE), and polyvinylidene fluoride-trifluoroethylene (PVdF-TrFE).

[0114] In an embodiment of the present invention, the separator may be manufactured by coating the separator substrate with the inorganic coating layer described above.

[0115] First, the binder material is dispersed or dissolved in a solvent to prepare a binder solution. Then, inorganic particles dispersed in a bead mill are added to the binder solution to prepare a slurry for forming an inorganic coating layer. Non-limiting examples of the solvent include one or a mixture of two or more selected from the group consisting of water, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and cyclohexane.

[0116] The method of coating the separator substrate with the slurry may be a conventional coating method known in the art, such as dip coating, die coating, roll coating, comma coating, or a mixture thereof. The drying may be any conventional drying method, such as natural drying or air drying, without any particular limitation.

[0117] According to yet another aspect of the present invention, an electrode assembly includes a positive electrode, a negative electrode, and a separator sandwiched between the positive electrode and the negative electrode, and the separator is any of the above-mentioned separators.

[0118] In this specification, specific components of the positive electrode, negative electrode, and electrode assembly may be conventional components, and therefore, description thereof will be omitted.

[0119] According to yet another aspect of the present invention, the electrode assembly prepared as described above can be placed in a suitable case and an electrolyte can be injected to provide a secondary battery.

[0120] The present invention will be described in more detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited thereto in any way.

[0121] [Separator substrate manufacturing] Example 1 9 kg of Cr-type polyolefin (TR570, DL Chemical, Korea) and 21 kg of diluent (LP350F, Kukdong Petrochemical, Korea) were fed into an extruder (φ32 twin-screw extruder, L / D=56, manufactured by EM, Korea) as raw materials, and melt-extruded at 200°C to obtain a polyolefin molten extrudate.

[0122] The obtained polyolefin melt extrudate was passed through a T-die, and then molded into a sheet using a cooling casting device, and then biaxially stretched in MD and then TD using a tenter-type sequential stretching machine to obtain a polyolefin sheet. The MD and TD stretch ratios were 7 times and 6 times, respectively, and the stretching temperatures were MD 115°C and TD 125°C.

[0123] The diluent was extracted from the stretched polyolefin sheet using methylene chloride to obtain a porous polyolefin sheet.

[0124] Next, a coating liquid containing 10 wt % of dicumyl peroxide as a thermal initiator in a solvent of ethanol was applied to one side of the porous polyolefin sheet.

[0125] The polyolefin sheet coated with the coating liquid was then dried and heat-set at 128° C. to produce a separator substrate in which a crosslinked structure was formed between vinyl groups in the polyolefin resin in the polyolefin sheet. The thickness of the separator substrate thus obtained was 9.0 μm.

[0126] Example 2 A separator substrate was produced in the same manner as in Example 1, except that 0.9 kg of Cr-type polyolefin and 8.1 kg of ZT-type polyolefin (VH350, manufactured by Daehan Petrochemical Co., Ltd., Korea) (containing magnesium (Mg) and aluminum (Al)) were used as raw materials (weight ratio of Cr-type:ZT-type=1:9). The thickness of the obtained separator substrate was 9.0 μm.

[0127] Example 3 A separator substrate was produced in the same manner as in Example 2, except that the Cr-type polyolefin:ZT-type polyolefin was used in a weight ratio of 3:7. The thickness of the obtained separator substrate was 9.0 μm.

[0128] Example 4 Except for using a weight ratio of 5:5 Cr-type polyolefin:ZT-type polyolefin, a separator substrate was produced in the same manner as in Example 2. The thickness of the obtained separator substrate was 9.0 μm.

[0129] Comparative Example 1 A separator substrate was produced in the same manner as in Example 1, except that a ZT-type polyolefin (VH035, manufactured by Daehan Petrochemical Co., Ltd., Korea) (containing magnesium (Mg) and aluminum (Al)) was used as the raw material instead of the Cr-type polyolefin, and the coating liquid application step was not performed. The thickness of the separator substrate obtained at this time was 9.1 μm.

[0130] Comparative Example 2 Except for not carrying out the coating liquid application step, a separator substrate was produced in the same manner as in Example 1. At this time, the thickness of the obtained separator substrate was 9.0 μm.

[0131] Comparative Example 3 A separator substrate was produced in the same manner as in Example 1, except that 0.45 kg of Cr-type polyolefin and 8.55 kg of ZT-type polyolefin (VH350, manufactured by Daehan Petrochemical Co., Ltd., Korea) (containing magnesium (Mg) and aluminum (Al)) were used as raw materials (weight ratio of Cr-type:ZT-type=0.5:9.5). The thickness of the obtained separator substrate was 9.0 μm.

[0132] [Analysis of separator substrate components and evaluation of physical properties] The components of Examples 1 to 4 and Comparative Examples 1 to 3 produced above were analyzed and their physical properties were evaluated as described below. The results are shown in Table 1 below.

[0133] [Measurement of gel fraction] First, 0.2 g of a separator substrate specimen was placed in a 120 mesh stainless steel net, extracted in trichlorobenzene at 100° C. for 12 hours, and then dried in a vacuum oven at 100° C. for 12 hours.

[0134] Then, the weight of the specimen remaining on the stainless steel net was measured, and the gel fraction was calculated according to the following formula: The gel fraction was expressed as the average value of the measured values ​​for each of three specimens. Gel fraction (%) = {(remaining specimen weight (g)) / 0.2 g} x 100

[0135] [Measurement of chromium content] First, the separator substrate specimen was reacted with sulfuric acid and carbonized (sulfated) on a hot plate, after which the sulfuric acid was removed. Then, it was incinerated in an electric furnace (temperature: 600℃) for 4 hours, and decomposed with nitric acid and hydrogen peroxide. Next, when the specimen was dissolved cleanly, it was diluted with tertiary ultrapure water to prepare an analysis sample.

[0136] The chromium (Cr) content in the separator substrate was measured using an inductively coupled plasma mass spectrometer (ICP-MS) (Axiom MC model, manufactured by Thermoelemental, UK).

[0137] [Measurement of aluminum (Al) content] When using a Ziegler-Natta catalyst, aluminum (Al) is present on the separator substrate, so the aluminum content was measured.

[0138] The aluminum content was measured in the same manner as that used to measure the chromium content.

[0139] [Break Temperature] The separator substrate produced above was analyzed for rupture temperature using a thermal mechanical analysis (TMA) device (manufactured by TA Instruments, TMA Q400).

[0140] Specifically, a load of 0.01 N was applied to the separator substrate, and the temperature was raised at a rate of 5°C / min while observing the degree of deformation. As the temperature was raised, the separator substrate contracted, and the temperature at which it stopped expanding again was measured as the "break temperature."

[0141] [Measurement of the number of spots] Separator base material 1m 2 The number of spots whose long sides were 50 μm or more per sample was visually counted.

[0142] [Measurement of thickness uniformity] The separator substrate was measured at 10 cm intervals over 1 m in the width direction, and at 3 m intervals over 30 m in the length direction, and the standard deviation of the thickness was calculated from the thickness measurements at a total of 100 positions.

[0143] [Table 1]

[0144] According to the results in Table 1 above, it was confirmed that the separator substrates of Examples 1 to 4, which were manufactured by using a Cr-type polyolefin resin as a raw material and applying a coating liquid containing a thermal initiator after extrusion of the resin, had a gel fraction of 35%, 11%, 17%, or 30%, respectively, a standard deviation of thickness of 0.5 μm or less, and a break temperature of 160° C. or more.

[0145] In contrast, the separator substrate of Comparative Example 1, which used only ZT-type polyolefin resin and was not coated with a coating liquid containing a thermal initiator, was poor in terms of gel fraction, rupture temperature, and thickness uniformity. Comparative Example 2, which used Cr-type polyolefin resin but was not coated with a coating liquid containing a thermal initiator, was still poor in terms of gel fraction and rupture temperature. Comparative Example 3, in which a small amount of Cr-type polyolefin resin was used, was confirmed to have a gel fraction of less than 3%.

[0146] The present invention has been described above with reference to an embodiment thereof. However, a person having ordinary knowledge in the technical field to which the present invention pertains should be able to make a wide variety of applications and modifications within the scope of the present invention based on the above content.

Claims

1. A separator substrate for an electrochemical device, comprising a crosslinked polyolefin resin and chromium (Cr), The separator substrate has a gel fraction of 3% to 80%; The standard deviation (Δd) of the thickness measured at any one of at least 100 points is 0.5 μm or less; 1m 2 The separator substrate for an electrochemical element has 10 or less spots each having a long side length of 50 μm or more.

2. 2. The separator substrate for an electrochemical element according to claim 1, wherein the chromium content is 0.1 ppm to 20 ppm.

3. 2. The separator substrate for an electrochemical element according to claim 1, wherein the separator substrate has a gel fraction of 3% to 50%.

4. 2. The separator substrate for an electrochemical element according to claim 1, wherein the crosslinked structure in the crosslinked polyolefin resin comprises a structure resulting from a radical polymerization reaction between vinyl groups mediated by a thermal initiator.

5. 5. The separator substrate for an electrochemical device according to claim 4, wherein the thermal initiator comprises a peroxide-based compound, a persulfate-based compound, an azo-based compound, or a mixture thereof.

6. 2. The separator substrate for an electrochemical element according to claim 1, further comprising at least one of titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), and vanadium (V).

7. 2. The separator substrate for an electrochemical element according to claim 1, wherein the standard deviation (Δd) of thickness measured at any one of at least 100 points on the separator substrate is 0.3 μm or less.

8. melt extruding a feed material comprising a polyolefin resin to obtain a polymeric melt extrudate; forming and stretching the resulting polymer melt extrudate to obtain a polymer sheet; applying a coating liquid containing a thermal initiator to the polymer sheet; drying and heat fixing the polymer sheet on which the coating liquid is applied; Including, The polyolefin resin includes a polyolefin resin produced using an olefin polymerization catalyst containing chromium, A method for producing a separator substrate for an electrochemical element, the separator substrate having a gel fraction of 3% to 80%.

9. 9. The method for producing a separator substrate for an electrochemical element according to claim 8, wherein the polyolefin resin in the raw material contains a polyolefin resin having 100 or more terminal vinyl groups per 1 million carbon atoms.

10. 9. The method for producing a separator substrate for an electrochemical element according to claim 8, wherein the raw material further comprises a polyolefin resin produced using an olefin polymerization catalyst that does not contain chromium and contains titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), vanadium (V), or two or more of these.

11. 11. The method for producing a separator substrate for an electrochemical device according to claim 10, wherein the content of the polyolefin resin produced using an olefin polymerization catalyst containing chromium is 10 wt% or more based on the total weight of the polyolefin resin in the raw material.

12. The separator substrate according to any one of claims 1 to 7, an inorganic coating layer formed on at least one surface of the separator substrate; Including, The separator for an electrochemical device, wherein the inorganic coating layer comprises inorganic particles and a binder material.

13. A positive electrode, a negative electrode, and a separator sandwiched between the positive electrode and the negative electrode, The electrode assembly, wherein the separator is as defined in claim 12.

Citation Information

Patent Citations

  • Separator for use in battery, method of fabricating the same, and alkaline battery

    JP2001167749A

  • Laminated microporous film, method for producing the same and separator for battery

    JP2011255654A

  • Lithium secondary battery including separator and method for manufacturing same

    JP2020527846A

  • Techniques for group signature

    KR102360944B1